Circulating MicroRNA-122-5p Is Associated With a Lack of Improvement in Left Ventricular Function After Transcatheter Aortic Valve Replacement and Regulates Viability of Cardiomyocytes Through Extracellular Vesicles. Issue 24 (8th July 2022) - Hosen, Mohammed Rabiul; Goody, Philip Roger; Zietzer, Andreas; Xiang, Xu; Niepmann, Sven Thomas; Sedaghat, Alexander; Tiyerili, Vedat; Chennupati, Ramesh; Moore, Joseph B.; Boon, Reinier A.; Uchida, Shizuka; Sinning, Jan-Malte; et al.
Abstract : Background: Transcatheter aortic valve replacement (TAVR) is a well-established treatment option for high- and intermediate-risk patients with severe symptomatic aortic valve stenosis. A majority of patients exhibit improvements in left ventricular ejection fraction (LVEF) after TAVR in response to TAVR-associated afterload reduction. However, a specific role for circulating microRNAs (miRNAs) in the improvement of cardiac function for patients after TAVR has not yet been investigated. Here, we profiled the differential expression of miRNAs in circulating extracellular vesicles (EVs) in patients after TAVR and, in particular, the novel role of circulating miR-122-5p in cardiomyocytes. Methods: Circulating EV-associated miRNAs were investigated by use of an unbiased Taqman-based human miRNA array. Several EV miRNAs (miR-122-5p, miR-26a, miR-192, miR-483-5p, miR-720, miR-885-5p, and miR-1274) were significantly deregulated in patients with aortic valve stenosis at day 7 after TAVR compared with the preprocedural levels in patients without LVEF improvement. The higher levels of miR-122-5p were negatively correlated with LVEF improvement at both day 7 ( r =−0.264 and P =0.015) and 6 months ( r =−0.328 and P =0.0018) after TAVR. Results: Using of patient-derived samples and a murine aortic valve stenosis model, we observed that the expression of miR-122-5p correlates negatively with cardiac function, which is associated with LVEF. Mice with graded wire injury–induced aortic valve stenosis demonstrated a higher level of miR-122-5p, which was related to cardiomyocyte dysfunction. Murine ex vivo experiments revealed that miR-122-5p is highly enriched in endothelial cells compared with cardiomyocytes. Coculture experiments, copy-number analysis, and fluorescence microscopy with Cy3-labeled miR-122-5p demonstrated that miR-122-5p can be shuttled through large EVs from endothelial cells into cardiomyocytes. Gain- and loss-of-function experiments suggested that EV-mediated shuttling of miR-122-5p increases the level of miR-122-5p in recipient cardiomyocytes. Mechanistically, mass spectrometry, miRNA pulldown, electrophoretic mobility shift assay, and RNA immunoprecipitation experiments confirmed that miR-122-5p interacts with the RNA-binding protein hnRNPU (heterogeneous nuclear ribonucleoprotein U) in a sequence-specific manner to encapsulate miR-122-5p into large EVs. On shuttling, miR-122-5p reduces the expression of the antiapoptotic gene BCL2 by binding to its 3′ untranslated region to inhibit its translation, thereby decreasing the viability of target cardiomyocytes. Conclusions: Increased levels of circulating proapoptotic EV-incorporated miR-122-5p are associated with reduced LVEF after TAVR. EV shuttling of miR-122-5p regulates the viability and apoptosis of cardiomyocytes in a BCL2-dependent manner.